ACEH FARMERS AGRICULTURAL BUSINESS PROBLEMS (Study of Aceh Peasant Judgment in the South West Coast Agricultural Zone) - Handayani, Sri; Nasution, Aswin (CV. Radja Publika, 2023)
Agriculture is an activity carried out as a fulfillment of various human needs, so it becomes an important sector to be maintained. In the implementation of agricultural business various problems are faced by farmers in the Southwest Region of Aceh. The results of research conducted using the Judgment Study show that there are 11 problems faced by farmers with 4 problems being above the average score, including agricultural development assistance from the government such as capital, superior seeds, production inputs, counseling and program supervision are not appropriate and complete ; agricultural development programs are not planned until a good market is available; it is difficult to get fertilizer, especially subsidized fertilizer, and the prices of agricultural products tend to be low and are detrimental to farmers. While 7 problems are below the average score with the lowest score problem being the plants that are developed are difficult to care for. Solving the problem is an effort to help farmers in running their agricultural business. This problem is also an obstacle in regional development, so that it can become the basis for planning in the implementation of regional development.